Crop raiding by olive baboon (Papio anubis) around Kainji lake national park, Nigeria (2015)
Human beings are known to be one of the major predators of baboon; either for consumption or as a form of pest control for their farmlands. Fields adjacent to protected areas are mostly affected by majority of baboon raids. This study investigated the crop raiding activities of Olive baboon (Papio anubis) around Kainji Lake National Park, Nigeria. Data were collected through administration of questionnaires to seventy-seven farmers in ten randomly selected villages. The study focused on farmers that encountered baboon on their farms and that showed a good knowledge of baboon as it was expected of them to be the most informative about crop raiding activities by Olive baboon. The results indicated that maize, yam and cassava were the mostly planted crops by the farmers. They were equally the mostly raided crops by olive baboon. They are favoured foods of primate crop raiders. Most of the raiding activities were carried out in the morning. The findings suggests that the bulk of the raiding would have been conducted very early in the morning with the aid of their cheek pouch used for food storage and to avoid persecution or predation by farmers latter in the day. Logically, majority of the farmers around Kainji Lake National Park adopted scaring as a means of controlling attack by baboons since most of the crop raidings were carried out before their arrival on the farm. This also demonstrates the farmers` level of tolerance. Future surveys should monitor the trend of tolerance and the rate at which the changes occur. Subsequent researches on crop raiding should extend the scope of study to assess any relationship between the distance of the farms to park boundary and extent of damage. Communities’ attitudes towards primate conservation need to be assessed as it has consequences on conservation efforts in protected areas. Park management should be more proactive in addressing human wildlife conflict to avoid animosity in support zone communities.